2021
DOI: 10.1007/s10493-021-00648-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variation of the cytochrome b DNA and protein sequences in Phytoseiulus macropilis and P. persimilis (Acari: Phytoseiidae) reflect population differentiation

Abstract: Several phytoseiid mite species are important natural enemies used in biological control strategies. In the present study, Cytb mtDNA sequences of various populations of two species, Phytoseiulus macropolis and P. persimilis, were compared to determine whether the specimens collected in Brazil could belong to P. persimilis as this latter species is reported in South America but not in Brazil. The Cytb marker was used because of its high evolution rate, assumed to capture intraspecific variation. No overlap bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These markers were chosen because previous studies proved their variability at intraspecific level in Phytoseiidae species (Dos Santos and Tixier, 2017;Tixier et al, 2010aTixier et al, , 2021Queiroz et al, 2021). DNA extractions were carried out on single female specimens, following the protocol accurately described in Kanouh et al (2010) and using the Qiagen modified process.…”
Section: Genetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…These markers were chosen because previous studies proved their variability at intraspecific level in Phytoseiidae species (Dos Santos and Tixier, 2017;Tixier et al, 2010aTixier et al, , 2021Queiroz et al, 2021). DNA extractions were carried out on single female specimens, following the protocol accurately described in Kanouh et al (2010) and using the Qiagen modified process.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…swirskii from Cape Verde, as previous studies suggested some link between genetic differences and biological features, e.g. climate adaptation (for COI and Cytb mtDNA) and prey adaptation (for 12S rRNA) (Tixier et al, 2010a(Tixier et al, , 2021Queiroz et al, 2021). Even if these markers are usually considered neutral, some studies have shown that mutations can be associated to abiotic factors (pesticide resistance in Tetranychus urticae (Koch) (Van Nieuwenhuyse et al, 2009;Fotoukkiaii et al, 2020), temperature adaptation in anchovies and Lottia in COI mtDNA sequences (Dong et al, 2009;Silva et al 2014)).…”
Section: Genetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation